Electric Vehicles and Their Charging Stations - Abuladze, Vasil (European Scientific Journal, ESJ, 2025)
By the end of the 20th century, the automotive industry faced new challenges, making the development of electric vehicles essential. The advantages of these vehicles are evident, particularly in their ecological benefits-such as reducing emissions, as electric vehicles do not produce exhaust, thereby improving air quality and decreasing environmental pollution. Additionally, they operate almost silently, reducing noise pollution and creating a more peaceful environment. Electric vehicles are also more energy-efficient than internal combustion engine vehicles, conserving energy and lowering costs. This paper focuses on studying the role, significance, development foundations, and outcomes of electric vehicles in the modern world. It examines the need for and the current dynamics of infrastructure development related to electric vehicles. Through qualitative and quantitative research methods, the paper assesses the degree to which Georgia aligns with other countries in terms of electric vehicle development, accessibility, and mobility. It explores the innovative advancements and the current state of development in Georgia in relation to the acquisition and movement of electric vehicles. Key findings show that the rise of electric transportation is largely influenced by governmental policies and infrastructure development. Countries such as Norway, Germany, the Netherlands, China, and Sweden have pioneered EV adoption through financial incentives, subsidies, and robust charging networks. These nations have set ambitious goals for transitioning to electric vehicles, such as Norway’s goal of 80% EV purchases and Sweden’s aim to have all new vehicles be emissions-free by 2030. In contrast, Georgia’s growing legislative framework supports the adoption of electric vehicles, with tax exemptions and infrastructure investments aimed at reducing urban air pollution.